Avaliação histológica, imunoistoquímica e biomecânica do osso ao redor de implantes com texturização de superfície produzida por oxidação eletrolítica por plasma e incorporada com Ca e P em ratas osteoporóticas - Nakasato, Karen Lumi [UNESP] (2017)
Osteoporosis is a systemic disease that modifies the bone metabolism and reduces the quantity and quality of bone tissue, resulting in lower bone density and commits the instalation success rate of osseointegrated implants. Thus, the currently trend is to develop and use microstructural modified Titanium implants for better physicochemical and biological properties to the peri-implant bone, allowing a suitable bone repair in critical areas. The objective of this study was to evaluate a new surface texturing tecnique using Plasma Electrolytic Oxidation (PEO) with Ca and P in rats with induced osteoporosis. 20 Wistar rats, female, adult, weighing 250 to 300 grams, were divided in two groups: PEO (textured implants by PEO with Ca and P incorporation) and AC (double etching-acid textured implants). Firstly, the rats were submitted to ovariectomy and after 90 days, implants were installed on each tibia, considering one implant belongs to PEO group and the other to the AC group. After 42 days of the implant installation, 10 animals were subjected to euthanasia and their tibias were decalcified for histological (hematoxylin and eosin staining) and immunohistochemical analysis, with primary antibodies against Osteoprotegerin (OPG), RANKL, Osteocalcin (OC) and TRAP. The other rats (n=10), after euthanasia, had their implants submitted to the reverse torque in digital torque wrench (N.cm). All the quantitative data were submitted to the normality test curve to establish the best statistical test (parametric or nonparametric), considering P<0.05 significance level. . The histological analysis showed that there was more bone neoformation in the PEO group when compared to the AC group. The immunohistochemical evaluation showed that the AC group had inferior results from the point of view of bone metabolism due to the slight immunolabeling of the OC protein. The other OPG, RANKL and TRAP proteins did not present...